2014
DOI: 10.5376/ijmeb.2014.04.0002
|View full text |Cite
|
Sign up to set email alerts
|

Ethnozoological Study of Traditional Medicinal Animals Used by the Kore People in Amaro Woreda, Southern Ethiopia

Abstract: A total of 90 people (practitioners) were interviewed from 15 kebeles. 25% of the respondents were female and 75% were male respondents. Questioners were also randomly distributed among selected government employees working in different offices. A total of 60 people (90% male and 10% female) were interviewed using semi-structured questionnaire. Independent samples t-test to compare means of quantitative data between male and female informants were computed using SPSS version 20. Chi-square test was computed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Out of the diverse body parts of the animals, visceral organs (bile, fat, tongue, juices, liver, rumen, spleen, pancreas) and animal products (egg, milk, butter, cheese, and honey,) have the highest proportion (N = 18, 20.45%), followed by meat (N = 13, 14.7%) used for remedial preparation. However, other similar ndings reported esh with the highest proportion (33.8%), followed by fat (11.5%), bone (8.6%), and blood (8.6%) (Dereje and Chane, 2014;Kendie et al, 2018).…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Out of the diverse body parts of the animals, visceral organs (bile, fat, tongue, juices, liver, rumen, spleen, pancreas) and animal products (egg, milk, butter, cheese, and honey,) have the highest proportion (N = 18, 20.45%), followed by meat (N = 13, 14.7%) used for remedial preparation. However, other similar ndings reported esh with the highest proportion (33.8%), followed by fat (11.5%), bone (8.6%), and blood (8.6%) (Dereje and Chane, 2014;Kendie et al, 2018).…”
Section: Discussionmentioning
confidence: 61%
“…A similar study done in Ethiopia indicated that, out of 51 animal species used therapeutically, 27(52.9%) were mammals, 9(17.6%) birds, 7(13.7%) arthropods, 6(11.76%) reptiles, and 1(1.96%) species each represented sh and annelids (Kendie et al, 2018). Dereje and Chane (2014) identi ed a total of 21 animal species, such as mammals, reptiles, and birds to prepare remedies for 46 ailments in the southern part of Ethiopia. Felipe et al (2013) was also observed the maximum quantity of mammalian species in zootherapeutic activity in Brazil.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations